Interdependency classification: a framework for infrastructure resilience - Negin Shamsi; Alysha Helmrich (Environmental Research: Infrastructure and Sustainability)
Critical Infrastructure Systems (CISs) provide essential services for nation-wide security, economy, and social well-being, and these systems are becoming increasingly interdependent to maintain those services. Recent and diverse disturbances worldwide have highlighted that interdependencies within CISs may increase the potential for cascading failures, amplifying the impacts of both large and small-scale disturbances into events of catastrophic proportions. The methodology involved conducting a literature search through scholarly databases and using a snowball approach to identify 12 relevant papers on infrastructure interdependencies. Thematic analysis was then applied to classify 50 interdependencies, which were synthesized into a unified classification system mapped to a foundational framework. The direct citation network visualization tool, Kumu, illustrated citation patterns and guided the analysis. Identifying and classifying various interdependencies, understanding their relationships, and assessing their role in CISs are crucial steps to prevent, mitigate, or manage unfavorable consequences and enhance system resilience. In this article, classifications of infrastructure interdependencies were compiled and identified and a unified classification was described. To support the resilience of CISs in periods of stability and instability, infrastructure managers not only need consistent terminology but a shared understanding of interdependencies to ensure said interdependencies within and across CISs are appropriately accounted for throughout the life cycle of infrastructure, from early planning stages to management—reactive or proactive—for disturbances. These are critical steps toward understanding how CISs operate in concert so infrastructure managers may sense and anticipate potential disruptions, manage the impacts and consequences, and adapt to changing future conditions.